Carbon is Forever: a Climate Change Experiment on Cooperation - Giacomo Calzolari; Marco Casari; Riccardo Ghidoni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
Greenhouse gases generate impacts that can last longer than human civilization itself. Such persistence may affect the behavioral ability to cooperate. Here we study mitigation efforts within a framework that reflects key features of climate change and then contrasts a dynamic versus a static setting. In a treatment with persistence, the pollution cumulates and generates damages over time while in another treatment it has only immediate effects and then disappears. We find that cooperation is not hampered, on average, by pollution persistence. Mitigation efforts, though, should not be delayed, because cooperation levels appear to deteriorate for high stocks of pollution.
Keywords: C70; C90; D03; Q54; 330